Comparison of the Effect of Morning Versus Night Amlodipine Administration on Blood Pressure Reduction in Primary Hypertensive Patients: Perbandingan Pengaruh Waktu Pemberian Amlodipin Pagi Versus Malam Terhadap Penurunan Tekanan Darah Pasien Hipertensi Primer - Eziah Ika Lubada; Selly Septi Fandinata; Rizky Darmawan (Journal Pharmasci (Journal of Pharmacy and Science), 2023)
Human blood pressure goes according to a circadian rhythm, blood pressure drops during sleep and increases in the morning this happens in most individuals. One of the hypertension drug therapies is Amlodipine Calcium Channel Blocker class which has a long half-life, so it can be used once a day, and amlodipine works as a long-acting antihypertensive. On reducing blood pressure in primary hypertensive patients. The design of this study was a cohort by measuring blood pressure before and after administration of amlodipine therapy in the morning or amlodipine at night in outpatients with a diagnosis of primary hypertension who received amlodipine therapy at the “X” Clinic in Surabaya with retrospective data collection. The results of this study were obtained from 20 patients who stated that there was no significant difference in difference in systolic and diastolic blood pressure between January and December 2019 in patients receiving amlodipine therapy 5 mg in the morning, 10 mg in the morning, 5 mg in the evening and 10 mg in the evening. There is an effect of giving amlodipine therapy in the morning and evening.